Mechanical properties of thiol-ene UV-curable thermoplastic polysilsesquioxanes - Lee, Albert S.; Jo, Young Yeol; Jeon, Hyeonyeol; Choi, Seung-Sock; Baek, Kyung-Youl; Hwang, Seung Sang (ELSEVIER SCI LTD, 2015)
A series of thiol-ene UV-curable inorganic organic hybrid polysilsesquioxanes of various phenyl:methacryloxypropyl and phenyl:mercaptopropyl copolymer compositions were synthesized in one-batch using a base-catalyzed system. These thermoplastic photocurable ladder-like structured materials were examined as scratch-resistant, hard-coating materials on both glass and PET substrates. The unique fully condensed structure of the hybrid polymers allowed for simplified processing and through variation of the organic functional group, films with high transparency, tunable refractive indices in the range of 1.467-1.546, pencil hardness values of 9H, and high nanoindentation modulus were obtained (7 GPa). These scratch-resistant polysilsesquioxanes may provide insight into the different organic functional group compositions which allow for optimal mechanical properties. (C) 2015 Published by Elsevier Ltd.
Keywords: HARD COATINGS; LADDERSILOXANES; POLYMERS